2015
DOI: 10.1080/19443994.2015.1033765
|View full text |Cite
|
Sign up to set email alerts
|

Removal of tetracycline using new biocomposites from aqueous solutions

Abstract: A B S T R A C TThis study investigated the removal of tetracycline (TC) using polypropylene (PP), polystyrene (PS), Saccharomyces cerevisiae (Sc) yeast, and new types of sorbents such as polypropylene-S. cerevisiae (PP-Sc) and Polystyrene-S. cerevisiae (PS-Sc) biocomposites from aqueous solutions in a batch system. PP-Sc and PS-Sc are newly synthesized yeast immobilized polymers for the removal of TC. The experimental results showed that the maximum TC removal was obtained by using the PP-Sc biocomposite, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 52 publications
1
8
0
1
Order By: Relevance
“…Similar conclusions were made by Erşan [29], who found that the optimum pH for the removal of TC on free Saccharomyces cerevisiae biomass, immobilized biomass on polypropylene and polystyrene was 6.0. The values of the pH PZC were found to be 5.338, 5.495 and 5.416, respectively.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Similar conclusions were made by Erşan [29], who found that the optimum pH for the removal of TC on free Saccharomyces cerevisiae biomass, immobilized biomass on polypropylene and polystyrene was 6.0. The values of the pH PZC were found to be 5.338, 5.495 and 5.416, respectively.…”
Section: Discussionsupporting
confidence: 86%
“…Erşan [29] studied the effect of adsorption time on TC adsorption on free and immobilized Saccharomyces cerevisiae biomass by varying the contact time from 2.5 to 240 min. At 100 mg L −1 initial TC concentration, 150 min optimum removal time was found, whereas a longer contact time (240 min) caused desorption [29]. Kip and Açıkel [30] reported that biosorption equilibrium during TC removal by Candida utilis immobilized on chitosan was reached for 240 min.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bu yöntemle Monvisade and Siriphannon çalışmasında kitosana kil (montmorillonite) ilave ederek hazırlanan kompozitin (Kitosan-MMT) katyonik boyalardaki adsorpsiyonunu incelemişlerdir [14]. Erşan polistiren ve Saccharomyces cerevisiae mayası ile hazırladığı sorbentleri kullanarak tetrasiklinin (TC) adsorpsiyonu çalışmasında en yüksek giderim 150 mg/L derişiminde 8,76 mg/g iken yaptığımız çalışmada 100 mg/L derişimde kitosan-Candida utilis biyokompozitinin TC adsorpsiyon kapasitesi pH 4'de 1,179 mg/g olarak bulunmuştur [15]. Atık sulardan ve yüksek derişimli ilaç (antibiyotik) içeren çözeltilerden TC'nin uzaklaştırılmasında kullanılan alternatif bir yöntem olan immobilize edilmiş biyokompozit malzemelerdir.…”
Section: Gi̇ri̇ş (Introduction)unclassified